Day by day armageddon - Bourne, J. L. (Pocket Books, 2009)
An ongoing journal depicting one man's personal struggle for survival, dealing with the trials of an undead world unfolding around him. An unknown plague sweeps the planet. The dead rise to claim the Earth as the new dominant species. Trapped in the midst of a global tragedy, he must make decisions ... choices that ultimately mean life, or the eternal curse to walk as one of them.